A modified generalized shift-splitting iteration method for complex symmetric linear systems. (July 2021) - Yan, Tongxin; Ma, Changfeng
Abstract: In this work, we introduce a modified generalized shift-splitting (MGSS) iteration method for a class of complex symmetric linear systems. Meanwhile, we establish the convergence analysis and give the spectral properties of the corresponding preconditioned matrix. Finally, a numerical example illustrates the effectiveness of the MGSS.